Scientific Review On Health Benefits Of Sleep Positions W.S.R To Left Side- Ayurvedic Perspective - Santosh , V R; Fathima, Noor (International Research Journal of Ayurveda & Yoga, 2020)
The Secrete of Health Maintenance and its Promotion have been old to mankind which is taught by Ayurveda. The Science of Life has always given prime importance to Health Maintenance. Sleep is a Physiological interruption of afferent pathways at a central point, humans spend almost a third of their lifetime in sleeping and number of vital physiological changes occur during sleep. Ayurveda considering sleep as one among Trayopasthamba ( Three sub pillars of life) and defines as due to klanta and Klama ( Quiescent stage) of mind body along with divorce of sense objects from the senses. Although the influence of sleep on health is well documented, but information about the body postures and its physiological importance is scare. The advice of left side sleeping position after food intake is recommended by Acharya Sushruta. Hence this paper aims to analyze different physiological changes occur during sleep which impart health by correcting if any metabolic dysfunction existing with special emphasize on left side sleep posture.